3D-printed superhard superflat novel polished tile and preparation method thereof

CN117185657BActive Publication Date: 2026-10-27FOSHAN LINGGAO NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310928325.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2026-10-27
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

[0003]因为抛釉砖最外层是玻璃晶体,导致其表面硬度不高,容易刮花和破损

Benefits of technology

[0025](1)本发明的抛光砖从下到上依次包括:坯体、底釉层、中间层、图案层和面料层;面料层所用的釉料包括小颗粒干粒、大颗粒干粒和粘合料,大小颗粒干粒混在面料层中,在后续烧结时,小颗粒干粒、大颗粒干粒下沉至中间层能减少颗粒在面料层表面停留,在自身重力作用下,小颗粒干粒先进行下陷,减少面料层表面颗粒凸出面料层表面,这样表面看起来更为平整,颗粒凸起较少。与现有的抛釉砖相比,本发明的抛光砖表面没有水波纹,而且由于面料层中包括大颗粒干粒和小颗粒干粒,其表面析晶后形成晶体颗粒,对光线形成漫反射,所以本发明的抛光砖也具有柔和不刺眼的光泽,具有高的表面硬度和耐磨性,表面还有一定的肌理感而且不损害表面平整度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117185657B_ABST
    Figure CN117185657B_ABST
Patent Text Reader

Abstract

The application discloses a 3D-printed superhard superflat novel polished tile and a preparation method thereof. The polished tile comprises, from bottom to top, a body, a bottom glaze layer, an intermediate layer, a pattern layer and a surface layer. The glaze used in the surface layer comprises small-particle dry particles, large-particle dry particles and a binding material. Compared with the existing glazed tile, the polished tile has no water ripples on the surface, and the surface is formed with crystal particles after crystallization due to the fact that the surface layer comprises the large-particle dry particles and the small-particle dry particles, so that the polished tile has a soft and non-stinging luster, high surface hardness and wear resistance, and a certain texture on the surface without damaging the surface flatness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of polished tiles, specifically to a novel 3D-printed ultra-hard and ultra-flat polished tile and its preparation method. Background Technology

[0002] Most common building decoration materials nowadays are glazed tiles. The glaze used in glazed tiles is a special formula glaze that can be polished on the surface. It is the last glaze applied to antique tiles. It is generally a transparent surface glaze or a transparent convex pattern glaze. Glazed tiles combine the advantages of polished tiles and antique tiles. The glaze surface is as smooth and bright as polished tiles, while the glaze pattern is as rich and colorful as antique tiles.

[0003] Because the outermost layer of glazed tiles is made of glass crystals, their surface hardness is not high, making them prone to scratches and damage. Furthermore, the glaze used in the production of glazed tiles is prone to water ripples, resulting in a relatively high defect rate and a lack of texture on the finished product surface. Summary of the Invention

[0004] To overcome the shortcomings of the prior art, one objective of this invention is to provide a novel 3D-printed ultra-hard and ultra-flat polished tile with no water ripples on its surface, high surface hardness, resistance to scratches, and the ability to maintain a certain texture. Another objective of this invention is to provide a method for preparing a novel 3D-printed ultra-hard and ultra-flat polished tile, which is simple in steps and suitable for large-scale production.

[0005] One of the objectives of this invention is achieved through the following technical solution:

[0006] A novel 3D-printed ultra-hard and ultra-flat polished tile comprises, from bottom to top: a body, a base glaze layer, an intermediate layer, a pattern layer, and a surface layer; the glaze used in the surface layer comprises the following components by weight percentage: SiO2 50-65%, Al2O3 6-20%, CaO 6-15%, K2O 1-10%, and Na2O 2-12%; wherein, the glaze used in the surface layer comprises small dry particles, large dry particles, and binder; the large dry particles include dry particles with a particle size of 18-30 mesh and dry particles with a particle size of 30-80 mesh, and the small dry particles include dry particles with a particle size of 100-250 mesh and dry particles with a particle size of 250-320 mesh. Preferably, the large dry granules include dry granules with a particle size of 18-30 mesh and dry granules with a particle size of 30-80 mesh in a mass ratio of (1-3):1, and the small dry granules include dry granules with a particle size of 100-250 mesh and dry granules with a particle size of 250-320 mesh in a mass ratio of (1-3):1. More preferably, the large dry granules include dry granules with a particle size of 18-30 mesh and dry granules with a particle size of 30-80 mesh in a mass ratio of 1:1, and the small dry granules include dry granules with a particle size of 100-250 mesh and dry granules with a particle size of 250-320 mesh in a mass ratio of 1:1.

[0007] Furthermore, the glaze used in the fabric layer comprises the following components by weight percentage: SiO2 50-65%, Al2O3 6-20%, CaO 6-15%, MgO 0.1-6%, K2O 1-6%, Na2O 2-7%, B2O3 0.1-6%, ZnO 0.1-10%, and BaO 0.1-6%.

[0008] Furthermore, the small dry particles account for 20-40% of the total dry particle mass, and the large dry particles account for 60-80% of the total dry particle mass.

[0009] Furthermore, the intermediate layer is a transparent glaze layer, which makes the outermost fabric layer more transparent. The hardness of the intermediate layer is less than that of the fabric layer.

[0010] Furthermore, the transparent glaze used in the transparent glaze layer comprises the following raw materials by weight percentage: 15-25% aluminum oxide, 40-50% silicon dioxide, 5-10% sodium oxide, 5-10% potassium oxide, 5-10% calcium oxide, 2-8% magnesium oxide, 2-8% boron trioxide, and 5-10% loss on ignition. Preferably, the transparent glaze comprises the following raw materials by weight percentage: 25% aluminum oxide, 34% silicon dioxide, 6% sodium oxide, 8% potassium oxide, 7% calcium oxide, 5% magnesium oxide, 5% boron trioxide, and 10% loss on ignition;

[0011] Furthermore, the binder comprises the following raw materials by weight percentage: 25-40% aluminum oxide, 40-60% silicon dioxide, 2-6% sodium oxide, 2-6% potassium oxide, 3-7% calcium oxide, 1-5% magnesium oxide, 1-5% strontium oxide, 1-5% barium oxide, 1-5% zinc oxide, and 2-10% loss on ignition, with the mass ratio of binder to total dry particles being (8-10):1.

[0012] Furthermore, the glaze used in the base glaze layer comprises the following raw materials by weight percentage: 50-55% feldspar, 12-20% nepheline powder, 4-6% quartz powder, 7-10% kaolin, 2-6% dolomite, 5-10% talc, 5-7% alumina, and 2-5% siliceous shale.

[0013] Furthermore, the raw materials used in the blank body include the following components by weight percentage: 45-50% water-milled abrasive, 4-6% diopside, 2-5% talc powder, 1-3% calcined talc, 7-9% potassium sodium stone powder, 2-3% bentonite, 20-30% black clay, and 5-10% ball clay.

[0014] The second objective of this invention is achieved by the following technical solution:

[0015] The above-mentioned method for preparing the 3D-printed ultra-hard and ultra-flat novel polished tile includes the following steps:

[0016] 1) Blank pressing and forming;

[0017] 2) Apply a base glaze to the surface of the blank, and form a base glaze layer after shaping;

[0018] 3) Spray glaze into the base glaze layer, and after setting, form the intermediate layer;

[0019] 4) 3D printing is performed on the intermediate layer to form a pattern layer;

[0020] 5) Mix large and small dry granules with the binder, apply the mixture to the pattern layer, and after setting, obtain the fabric layer. Specific application methods include, but are not limited to, dry or wet methods. When using the dry method, after spreading the mixture evenly on the pattern layer, a setting adhesive is sprayed to bond and fix the mixture. The setting adhesive is a 0.8–1.5% (w / w) carboxymethyl cellulose (CMC) aqueous solution. When using the wet method, a suspending agent is added to the mixture to form a slurry, which is then spread on the pattern layer. After drying, the fabric layer is obtained.

[0021] 6) After sintering and cooling, the surface of the fabric layer is ground smooth to obtain a new type of 3D-printed ultra-hard and ultra-flat polished tile.

[0022] Furthermore, the height of the pattern layer is 0.5 to 1.5 mm, preferably 1 mm.

[0023] Further, in step 6), the sintering temperature is 1150–1200℃, and the sintering time is 10–20 min. The initial melting point of the two dry granules used in the fabric layer is 900–950℃, preferably 930℃.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] (1) The polished tile of the present invention comprises, from bottom to top: a body, a base glaze layer, an intermediate layer, a pattern layer, and a surface layer; the glaze used in the surface layer includes small dry particles, large dry particles, and a binder. The small and large dry particles are mixed in the surface layer. During subsequent sintering, the small and large dry particles sink to the intermediate layer, which reduces the particles remaining on the surface of the surface layer. Under their own gravity, the small dry particles sink first, reducing the number of particles protruding from the surface of the surface layer. This makes the surface appear smoother with fewer particle protrusions. Compared with existing glazed tiles, the polished tile of the present invention has no water ripples on the surface. Moreover, because the surface layer includes large and small dry particles, crystallization on its surface forms crystalline particles, which diffusely reflect light. Therefore, the polished tile of the present invention also has a soft, non-glaring gloss, high surface hardness and wear resistance, and a certain texture without compromising surface smoothness.

[0026] (2) The glaze used in the fabric layer of the present invention requires the mixing and filling of large and small dry particles with binder. During subsequent high-temperature firing, the gas will be discharged through the gap between the dry particles and the binder. Therefore, the fabric layer is not easy to retain gas during sintering and is not easy to generate bubbles, thus maintaining good surface flatness of the fabric layer.

[0027] (3) In the preparation method of the polished tile of the present invention, after forming a base glaze layer and an intermediate layer on the green body in sequence, a pattern layer is formed on the intermediate layer by 3D printing. The pattern is a three-dimensional raised pattern. Then, a mixture of large dry granules, small dry granules and binder is applied to the surface of the pattern layer. After shaping, a surface layer is obtained. Then, sintering is carried out. By controlling the initial melting point and firing temperature, the small dry granules are completely melted while the large dry granules are not completely melted, so that the surface layer and the pattern layer become one. After sintering, the surface is ground and polished to produce a unique texture. Moreover, due to the polishing treatment, the surface has good flatness and good gloss. Attached Figure Description

[0028] Figure 1 This is a diagram showing the layered structure of the polished brick in this invention;

[0029] Figure 2 The image shows a physical photograph of the polished tile from Example 1.

[0030] Figure 3 The image shows a physical example of the polished tile used in Comparative Example 1.

[0031] Figure 4 The image shows a physical example of the polished tile used in Comparative Example 2.

[0032] Figure 5 This is a picture of a commercially available glazed tile.

[0033] Figure 1 The layers are: 1. Body; 2. Base glaze layer; 3. Intermediate layer; 4. Pattern layer; 5. Top layer. Detailed Implementation

[0034] The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0035] Example 1

[0036] like Figure 1As shown, a novel 3D-printed ultra-hard and ultra-flat polished tile comprises, from bottom to top: a body 1, a base glaze layer 2, an intermediate layer 3, a pattern layer 4, and a surface layer 5. The glaze used in the surface layer 5 comprises the following components by weight percentage: SiO2 55%, Al2O3 18%, CaO 10%, MgO 4%, K2O 2%, Na2O 5%, B2O3 2%, ZnO 2%, and BaO 2%. The glaze used in the surface layer 5 includes small dry particles, large dry particles, and a binder. The large dry particles include 25-mesh and 60-mesh dry particles in a 1:1 mass ratio, and the small dry particles include 200-mesh and 300-mesh dry particles in a 1:1 mass ratio. The small dry particles account for 50% of the total dry particle mass, and the large dry particles account for 50% of the total dry particle mass. The initial melting point of both types of dry granules is 930℃, and the intermediate layer 3 is a transparent glaze layer. The mass ratio of binder to total dry granules is 9:1. The hardness of the intermediate layer 3 is less than that of the fabric layer 5.

[0037] Specifically, the glaze used in the base glaze layer 2 comprises the following raw materials by weight percentage: feldspar 52%, nepheline powder 14%, quartz powder 5%, kaolin 8%, dolomite 4%, talc 8%, alumina 6%, and siliceous shale 3%. The raw materials used in the body 1 comprise the following components by weight percentage: water-polished abrasive 46%, diopside 5%, talc powder 3%, calcined talc 2%, potassium sodium silicate powder 8%, bentonite 2%, black clay 25%, and ball clay 9%. The transparent glaze used in the transparent glaze layer comprises the following raw materials by weight percentage: alumina 15%, silicon dioxide 44%, sodium oxide 6%, potassium oxide 8%, calcium oxide 7%, magnesium oxide 5%, boron trioxide 5%, and loss on ignition 10%. The binder comprises the following raw materials by weight percentage: 28% aluminum oxide, 45% silicon dioxide, 3% sodium oxide, 4% potassium oxide, 4% calcium oxide, 3% magnesium oxide, 3% strontium oxide, 2% barium oxide, 2% zinc oxide, and 6% loss on ignition.

[0038] The above-mentioned method for preparing the 3D-printed ultra-hard and ultra-flat novel polished tile includes the following steps:

[0039] 1) The blank 1 is pressed and formed;

[0040] 2) Apply a base glaze to the surface of the blank 1, and after setting, form a base glaze layer 2 to cover the blank 1;

[0041] 3) Spray glaze into the base glaze layer 2, and after setting, form the intermediate layer 3;

[0042] 4) 3D printing is performed on the intermediate layer 3. After drying, the pattern is fixed to form the pattern layer 4. The pattern is a stripe with a three-dimensional raised shape and the height of the stripe is 1mm.

[0043] 5) Mix the large dry granules, small dry granules and adhesive to obtain a mixture. Spread the mixture evenly on the pattern layer 4 and spray setting adhesive to bond and fix the large dry granules, small dry granules and adhesive to obtain the fabric layer 5. The fabric layer 5 and the striped pattern layer 4 become one. The setting adhesive is a 1% carboxymethyl cellulose (CMC) aqueous solution.

[0044] 6) Sinter at 1180℃ for 15 minutes, cool, and then grind the surface of fabric layer 5 smooth to obtain the desired result. Figure 2 The image shows a novel 3D-printed ultra-hard, ultra-flat polished tile.

[0045] Example 2

[0046] like Figure 1 As shown, a novel 3D-printed ultra-hard and ultra-flat polished tile comprises, from bottom to top: a body 1, a base glaze layer 2, an intermediate layer 3, a pattern layer 4, and a surface layer 5. The glaze used in the surface layer 5 comprises the following components by weight percentage: SiO2 52%, Al2O3 20%, CaO 15%, K2O 6%, and Na2O 7%. The glaze used in the surface layer 5 includes small dry granules, large dry granules, and a binder. The large dry granules include 18-mesh and 30-mesh dry granules in a 2:1 mass ratio, and the small dry granules include 100-mesh and 250-mesh dry granules in a 3:1 mass ratio. The small dry granules account for 20% of the total dry granule mass, and the large dry granules account for 80% of the total dry granule mass. The initial melting point of the two types of dry granules is 900℃. The intermediate layer 3 is a transparent glaze layer. The mass ratio of binder to total dry particles is 8:1. The hardness of the intermediate layer 3 is less than that of the top layer 5.

[0047] Specifically, the glaze used in the base glaze layer 2 comprises the following raw materials by weight percentage: feldspar 55%, nepheline powder 20%, quartz powder 4%, kaolin 7%, dolomite 2%, talc 5%, alumina 5%, and siliceous shale 2%. The raw materials used in the body 1 comprise the following components by weight percentage: water-polished abrasive 45%, diopside 6%, talc powder 4%, calcined talc 3%, potassium sodium silicate powder 9%, bentonite 3%, black clay 20%, and ball clay 10%. The transparent glaze used in the transparent glaze layer comprises the following raw materials by weight percentage: alumina 20%, silicon dioxide 30%, sodium oxide 5%, potassium oxide 8%, calcium oxide 6%, magnesium oxide 8%, boron trioxide 8%, and loss on ignition 15%. The binder comprises the following raw materials by weight percentage: 25% aluminum oxide, 40% silicon dioxide, 2% sodium oxide, 4% potassium oxide, 7% calcium oxide, 5% magnesium oxide, 5% strontium oxide, 5% barium oxide, 5% zinc oxide, and 2% loss on ignition.

[0048] The above-mentioned method for preparing the 3D-printed ultra-hard and ultra-flat novel polished tile includes the following steps:

[0049] 1) The blank 1 is pressed and formed;

[0050] 2) Apply a base glaze to the surface of the blank 1, and after setting, form a base glaze layer 2 to cover the blank 1;

[0051] 3) Spray glaze into the base glaze layer 2, and after setting, form the intermediate layer 3;

[0052] 4) 3D printing is performed on the intermediate layer 3. After drying, the pattern is fixed to form the pattern layer 4. The pattern is a stripe with a three-dimensional raised shape and the height of the stripe is 0.5mm.

[0053] 5) Mix large dry granules, small dry granules and binder to obtain a mixture, then add a suspending agent to the mixture to form a slurry, spread the slurry evenly on the pattern layer 4, and after drying, obtain the fabric layer 5; the fabric layer 5 and the striped pattern layer 4 become one.

[0054] 6) Sinter at 1150℃ for 20 minutes, cool, and then grind the surface of the fabric layer 5 to obtain a new type of 3D-printed ultra-hard and ultra-flat polished tile.

[0055] Example 3

[0056] like Figure 1 As shown, a novel 3D-printed ultra-hard and ultra-flat polished tile comprises, from bottom to top: a body 1, a base glaze layer 2, an intermediate layer 3, a pattern layer 4, and a surface layer 5. The glaze used in the surface layer 5 comprises the following components by weight percentage: SiO2 55%, Al2O3 10%, CaO 10%, MgO 1%, K2O 4%, Na2O 5%, B2O3 4%, ZnO 5%, and BaO 6%. The glaze used in the surface layer 5 includes small dry particles, large dry particles, and binder. The large dry particles include dry particles with a particle size of 30 mesh and dry particles with a particle size of 30-80 mesh in a mass ratio of 3:1. The small dry particles include dry particles with a particle size of 100-250 mesh and dry particles with a particle size of 250-320 mesh in a mass ratio of 2:1. The small dry granules account for 40% of the total dry granule mass, and the large dry granules account for 60% of the total dry granule mass. The initial melting point of both types of dry granules is 950°C, and the intermediate layer 3 is a transparent glaze layer. The mass ratio of the binder to the total dry granules is 10:1. The hardness of the intermediate layer 3 is less than that of the fabric layer 5.

[0057] Specifically, the glaze used in the base glaze layer 2 comprises the following raw materials by weight percentage: feldspar 50%, nepheline powder 12%, quartz powder 4%, kaolin 10%, dolomite 6%, talc 5%, alumina 10%, and siliceous shale 3%. The raw materials used in the body 1 comprise the following components by weight percentage: water-polished abrasive 50%, diopside 4%, talc powder 2%, calcined talc 1%, potassium sodium silicate powder 7%, bentonite 2%, black clay 29%, and ball clay 5%. The transparent glaze used in the transparent glaze layer comprises the following raw materials by weight percentage: alumina 25%, silicon dioxide 40%, sodium oxide 5%, potassium oxide 6%, calcium oxide 10%, magnesium oxide 2%, boron trioxide 2%, and loss on ignition 10%. The binder comprises the following raw materials by weight percentage: 37% aluminum oxide, 40% silicon dioxide, 5% sodium oxide, 5% potassium oxide, 4% calcium oxide, 1% magnesium oxide, 1% strontium oxide, 1% barium oxide, 1% zinc oxide, and 5% loss on ignition.

[0058] The above-mentioned method for preparing the 3D-printed ultra-hard and ultra-flat novel polished tile includes the following steps:

[0059] 1) The blank 1 is pressed and formed;

[0060] 2) Apply a base glaze to the surface of the blank 1, and after setting, form a base glaze layer 2 to cover the blank 1;

[0061] 3) Spray glaze into the base glaze layer 2, and after setting, form the intermediate layer 3;

[0062] 4) 3D printing is performed on the intermediate layer 3. After drying, the pattern is fixed to form the pattern layer 4. The pattern is a stripe with a three-dimensional raised shape and the height of the stripe is 2mm.

[0063] 5) Mix the large dry granules, small dry granules and adhesive to obtain a mixture. Spread the mixture evenly on the pattern layer 4 and spray setting glue to bond and fix the large dry granules, small dry granules and adhesive to obtain the fabric layer 5. The fabric layer 5 becomes one with the striped pattern.

[0064] 6) Sinter at 1200℃ for 10 minutes, cool, and then grind the surface of the fabric layer 5 to obtain a new type of 3D-printed ultra-hard and ultra-flat polished tile.

[0065] Comparative Example 1

[0066] The difference between Comparative Example 1 and Example 1 is that the glaze used in the fabric layer 5 of Comparative Example 1 includes large dry granules and binder; the particle size of the large dry granules is 25 mesh. The amount of dry granules added is the same as in Example 1. The remaining components and preparation methods are also the same as in Example 1. A physical image of the polished tile of Comparative Example 1 can be found here. Figure 3 .

[0067] Comparative Example 2

[0068] The difference between Comparative Example 2 and Example 1 is that the glaze used in the fabric layer 5 of Comparative Example 2 includes small dry granules and binder; the particle size of the small dry granules is 300 mesh. The amount of dry granules added is the same as in Example 1. The remaining components and preparation method are also the same as in Example 1. A physical image of the polished tile of Comparative Example 1 can be found here. Figure 4 .

[0069] Comparative Example 3

[0070] Comparative Example 3 consists of glazed polished tiles purchased from Foshan Dengyu Technology Co., Ltd. A picture of the actual glazed polished tiles is shown below. Figure 5 As shown.

[0071] I. Texture Effect

[0072] Depend on Figures 2-5 As shown, the polished tile of Example 1 has a distinct textured surface, but its surface gloss is not as high as that of the glazed tile. This is because the fabric layer 5 includes both large and small dry granules, which crystallize on the surface to form crystalline particles, resulting in diffuse reflection of light. The polished tiles in Comparative Examples 1 and 2 do not exhibit a textured surface, indicating that only a fabric layer 5 containing both large and small dry granules can achieve this textured effect. Comparative Example 3 is a glazed tile; although its pattern differs from that of Example 1, the surface of the glazed tile is a glassy crystal surface, resulting in better gloss and brightness, but it lacks a textured surface.

[0073] II. Hardness Test

[0074] Testers conducted Mohs hardness tests on Examples 1-3 and Comparative Examples 1-3, respectively. The specific testing method was as follows: 10 ceramic tiles of known Mohs hardness were selected for each group. The standards were: talc grade 1, gypsum grade 2, calcite grade 3, fluorite grade 4, apatite grade 5, feldspar grade 6, quartz grade 7, topaz grade 8, corundum grade 9, and diamond grade 10. The level of hardness that caused the damage to the glaze of each tile was observed, and the hardness was expressed as the measured scratch depth. Specific data are shown in Table 1.

[0075] Table 1. Mohs hardness data for each group

[0076]

[0077]

[0078] As shown in Table 1, the polished tiles of Examples 1-3 have a Mohs hardness of up to 6, which is higher than that of commercially available glazed tiles. The hardness of Comparative Examples 1-2 is not much different from that of Example 1, indicating that the dry particle size in the surface layer 5 does not affect the hardness of the polished tile, but only its appearance.

[0079] III. Abrasion Resistance Test

[0080] Testers conducted abrasion resistance tests on Examples 1-3 and Comparative Examples 1-3, respectively. The abrasion resistance test of ceramic tiles was mainly conducted according to the "Test Methods for Ceramic Tiles Part VII" (GB / T3810.7—2016). The principle is as follows: the abrasion resistance of ceramic tiles is tested by placing and rotating an abrasive medium on the glazed surface, comparing and contrasting the abraded ceramic tile samples with unaffected samples, and evaluating the abrasion resistance of the marble. The abrasion resistance grading standards for the products are shown in Table 2. The abrasion resistance grading data for each group of products are shown in Table 3.

[0081] Table 2 Marble Abrasion Resistance Grading

[0082]

[0083] Table 3. Abrasion resistance data for each group of marble products

[0084] Example 1 Level 4, 2100 RPM Example 2 Level 3 1500 RPM Example 3 Level 4, 2100 RPM Comparative Example 1 Level 3 1500 RPM Comparative Example 2 Level 3 1500 RPM Comparative Example 3 Level 3 750 RPM

[0085] As shown in Table 3, the abrasion resistance levels of the polished tiles in Examples 1-3 and Comparative Examples 1-2 are all higher than Level 3 (1500 revolutions or more), indicating that the polished tiles of the present invention have excellent anti-abrasion effects. The glazed tile in Comparative Example 3 meets the Level 3 standard of 750 revolutions, reaching the factory standard, but its abrasion resistance is lower than that of the polished tiles in Examples 1-3 and Comparative Examples 1-2.

[0086] In summary, compared with existing glazed tiles, the polished tiles of Examples 1-3 do not have water ripples in their glaze. Moreover, since the surface layer 5 includes large and small dry granules, crystallization on its surface forms crystalline particles, which diffusely reflect light. Therefore, the polished tiles of the present invention also have a soft, non-glaring gloss, high surface hardness and wear resistance, and a certain texture without compromising surface flatness.

[0087] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.

Claims

1. A 3D-printed ultra-hard, ultra-flat polished tile, characterized in that, From bottom to top, it includes: a body, a base glaze layer, an intermediate layer, a pattern layer, and a top layer; the intermediate layer is a transparent glaze layer, and its hardness is less than that of the top layer; the glaze used in the top layer includes the following components by weight percentage: SiO2 50-65%, Al2O3 6-20%, CaO 6-15%, K2O 1-6% and Na2O 2-12%; wherein, the glaze used in the fabric layer includes small dry particles, large dry particles, and binder; the large dry particles include dry particles with a particle size of 18-30 mesh and dry particles with a particle size of 30-80 mesh, and the small dry particles include dry particles with a particle size of 100-250 mesh and dry particles with a particle size of 250-320 mesh; wherein, the small dry particles account for 20-40% of the total dry particle mass, and the large dry particles account for 60-80% of the total dry particle mass; the binder includes the following raw materials by weight percentage: 25-40% aluminum oxide, 40-60% silicon dioxide, 2-6% sodium oxide, 2-6% potassium oxide, 3-7% calcium oxide, 1-5% magnesium oxide, 1-5% strontium oxide, 1-5% barium oxide, 1-5% zinc oxide, and 2-10% loss on ignition, and the mass ratio of binder to total dry particles is (8-10):

1.

2. The 3D-printed ultra-hard, ultra-flat polished tile as described in claim 1, characterized in that, The glaze used in the fabric layer comprises the following components by weight percentage: SiO2 50-65%, Al2O3 6-20%, CaO 6-15%, MgO 0.1-6%, K2O 1-6%, Na2O 2-7%, B2O3 0.1-6%, ZnO 0.1-10%, and BaO 0.1-6%.

3. The 3D-printed ultra-hard, ultra-flat polished tile as described in claim 1, characterized in that, The transparent glaze used in the transparent glaze layer comprises the following raw materials by weight percentage: 15-25% aluminum oxide, 40-50% silicon dioxide, 5-10% sodium oxide, 5-10% potassium oxide, 5-10% calcium oxide, 2-8% magnesium oxide, 2-8% boron trioxide, and 5-10% loss on ignition.

4. The 3D-printed ultra-hard, ultra-flat polished tile as described in claim 1, characterized in that, The glaze used in the base glaze layer comprises the following raw materials by weight percentage: feldspar 50-55%, nepheline powder 12-20%, quartz powder 4-6%, kaolin 7-10%, dolomite 2-6%, talc 5-10%, alumina 5-7%, and siliceous shale 2-5%; the raw materials used in the body comprise the following components by weight percentage: water-polished material 45-50%, diopside 4-6%, talc powder 2-5%, calcined talc 1-3%, potassium sodium stone powder 7-9%, bentonite 2-3%, black clay 20-30%, and ball clay 5-10%.

5. The method for preparing the 3D-printed ultra-hard, ultra-flat polished tile according to any one of claims 1 to 4, characterized in that, Includes the following steps: 1) Blank pressing and forming; 2) Apply a base glaze to the surface of the blank, and form a base glaze layer after shaping; 3) Spray glaze into the base glaze layer, and after setting, form the intermediate layer; 4) 3D printing is performed on the intermediate layer to form a pattern layer; 5) Mix large dry granules, small dry granules and adhesive, apply to the pattern layer, and after setting, obtain the fabric layer. 6) After sintering and cooling, the surface of the fabric layer is ground smooth to obtain a 3D printed ultra-hard and ultra-flat polished tile.

6. The method for preparing the 3D-printed ultra-hard, ultra-flat polished tile as described in claim 5, characterized in that, The height of the pattern layer is 0.5 to 1.5 mm.

7. The method for preparing 3D-printed ultra-hard, ultra-flat polished tiles as described in claim 5, characterized in that, Step 6), the sintering temperature is 1150~1200℃, and the sintering time is 10~20min.

Citation Information

Patent Citations

  • Ceramic tile with dry particle glaze-decorated surface and manufacturing method thereof

    CN103626523A

  • Slate ceramic tile with diamond gloss effect and preparation method thereof

    CN109761649A

  • Reticulated ceramic tile and preparation method thereof

    CN116354745A